Effects of dietary tryptophan on cannibalism, survival and growth of Wallago attu (Bloch & Schneider, 1801) juveniles - Vo, Duc Nghia; Le, Tien Huu; Le, Thi Thu An; Nguyen, Van Huy (Hue University Journal of Science: Natural Science, 2022)
This study aims to evaluate the effects of supplemented commercial diets with tryptophan (TRP) on plasma serotonin, cannibalism, survival rate, and growth of Wallago attu (helicopter catfish). After one week of acclimation, 3,200 juveniles of helicopter catfish (BW = 2.5 ± 0.27 g, total length = 5.6 ± 0.43 cm) were randomly assigned for the experiment in fifteen plastic tanks (200 L). The experiment was conducted with five treatments (CT – 0 g TRP/kg – control group, T1 – 5 g TRP/kg, T2 – 10 g TRP/kg, T3 – 20 g TRP/kg, and T4 – 40 g TRP/kg) in a completely randomized design with three replications for four weeks. The results from the enzyme-linked immunosorbent assay reveal that TRP-supplemented diets effectively increased the serotonin level (5-HT) in the plasma of the catfish. The serotonin level increased with the dose of TRP added to the feed. Furthermore, a higher TRP level significantly decreased cannibalism and improved the final survival of the fish. However, the fish’s growth rate among treatments T1, T2, T3, and T4 was not significantly different, but there was a statistical difference between the experimental treatments and the CT treatment. The findings of this study suggest that TRP could be supplemented at a dose of 20 g·kg–1 to the feed to reduce cannibalism and improve the final survival of helicopter catfish.